Prospects for distinguishing galaxy evolution models with surveys at redshifts z ≳ 4. Issue 3 (13th October 2020) - Mirocha, Jordan
ABSTRACT: Many semi-empirical galaxy formation models have recently emerged to interpret high- z galaxy luminosity functions and make predictions for future galaxy surveys. A common approach assumes a 'universal' star formation efficiency, f *, independent of cosmic time but strongly dependent on the masses of dark matter haloes. Though this class of models has been very successful in matching observations over much of cosmic history, simple stellar feedback models do predict redshift evolution in f * and are commonly used in semi-analytic models. In this work, we calibrate a set of universal f * and feedback-regulated models to the same set of rest-ultraviolet z  ≳ 4 observations and find that a rapid, ∼(1 + z ) −3/2 decline in both the efficiency of dust production and duty cycle of star formation are needed to reconcile feedback-regulated models with current observations. By construction, these models remain nearly identical to universal f * models in rest-ultraviolet luminosity functions (UVLFs) and colours. As a result, the only way to distinguish these competing scenarios is either via (i) improved constraints on the clustering of galaxies – universal and feedback-regulated models differ in predictions for the galaxy bias by 0.1 ≲ Δ〈 b 〉 ≲ 0.3 over 4 ≲ z  ≲ 10 – or (ii) independent constraints on the dust contents and/or duty cycle of star formation. This suggests that improved constraints on the 'dustiness' and 'burstiness' of high- z galaxies will not merely add clarity to a given model of star formation in high- z galaxies, but rather fundamentally determine our ability to identify the correct model in the first place.